Menumbuhkan Kesadaran dan Semangat Bela Negara Melalui Kegiatan Sosial pada Panti Asuhan Kafilul Yatim Nurul Falah - Kanza Armifa Angia Said; Rabiatuladawiyah, Adinda; Natalia, Wira; Asri, Annisa; Sinaga, Sandra Jesica; Clarensia, Sagita; Oktavia, Khalisah; Julio, Gibraldo; Fahtoni, Syahri; Muhammad, Musyaffa’; Ramadhan, Davinnizam (LPPM UPN Veteran Jakarta, 2023)
Every child of the nation, regardless of economic background, family, and place of residence, deserves to be given education and inspiration related to defending the country. This made the UPN